Hsp70 overexpression in Drosophila hemocytes attenuates benzene‐induced immune and developmental toxicity via regulating ROS/JNK signaling pathway. Issue 7 (18th March 2022) - D'Souza, Leonard Clinton; Dwivedi, Shiwangi; Raihan, Faiza; Yathisha, Undiganalu Gangadharappa; Raghu, Shamprasad Varija; Mamatha, Bangera Sheshappa; Sharma, Anurag
Abstract: Benzene, a ubiquitous environmental chemical, is known to cause immune dysfunction and developmental defects. This study aims to investigate the relation between benzene‐induced immune dysfunction and developmental toxicity in a genetically tractable animal model, Drosophila melanogaster . Further, the study explored the protective role of Heat Shock Protein 70 (Hsp70) against benzene‐induced immunotoxicity and subsequent developmental impact. Drosophila larvae exposed to benzene (1.0, 10.0, and 100.0 mM) were examined for total hemocyte (immune cells) count, phagocytic activity, oxidative stress, apoptosis, and their developmental delay and reduction were analyzed. Benzene exposure for 48 h reduced the total hemocytes count and phagocytic activity, along with an increase in the Reactive Oxygen Species (ROS), and lipid peroxidation in the larval hemocytes. Subsequently, JNK‐dependent activation of the apoptosis (Caspase‐3 dependent) was also observed. During their development, benzene exposure to Drosophila larvae led to 3 days of delay in development, and ~40% reduced adult emergence. Hsp70‐ overexpression in hemocytes was found to mitigate benzene‐induced oxidative stress and abrogated the JNK‐mediated apoptosis in hemocytes, thus restoring total hemocyte count and improving phagocytotic activity. Further, hsp70‐ overexpression in hemocytes also lessened the benzene‐induced developmental delay (rescue of 2.5 days) and improved adult emergence (~20%) emergence, revealing a possible control of immune cells on the organism's development and survival. Overall, this study established that hsp70‐ overexpression in the Drosophila hemocytes confers protection against benzene‐induced immune injury via regulating the ROS/JNK signaling pathway, which helps in the organism's survival and development.